Plantas do planeamento urbano e do urbanismo em Portugal (1864-1926) - Fernandes, Mário Gonçalves (2021)
In the continuity of the longstanding, important and well-known practice of urbanism in Portugal (from the Middle Ages to the Renaissance and the 18th century of the Marquis de Pombal), as was the case generally throughout Europe, urban planning was only institutionalized in the second half of the 19th century. In the socioeconomic and cultural context of the government of Fontes Pereira de Melo, the engineer, Joa o Chrysostomo de Abreu e Sousa, passed a Decree-Law on 31st December 1864, in which the "general improvement plans" were instituted and, although only applicable to the Lisbon and Porto City Halls, it provided guidelines and rules for the others, leading to the development of plans for many Portuguese cities, some dating still from the 1800s and others from the first republic (after 1910). Thus, several City Halls felt the need to develop initiatives to obtain precise cartography of their municipalities. Indeed, one can say it became a common denominator to municipal action and, considering the known documents, Portugal entered the first phase of the generalized production of scientific urban cartography in the mid-1800s, prepared as a means to support urban planning actions. Previously, a majority of the illustrations viewed the urban agglomeration as a cultural or military object, whereas later we find a larger number of Portuguese settlements with cartography covering the city as a whole, with the urban agglomeration as its object and urban planning and transformation as its objective